Molecular analysis of a polypeptide of the RmS-17 protein for the development of a vaccine against Rhipicephalus microplus ticks in Mexico - Martínez-Maza, Nayely Teresa; Hernández-Ortiz, Rubén; Valdez-Espinoza, Uriel Mauricio; Castro-Saines, Edgar; Aguilar-Díaz, Hugo; Lagunes Quintanilla, Rodolfo Esteban (Ecosistemas y Recursos Agropecuarios, 2020)
The aim of this work was to analyze a RmS-17 polypeptide from  Rhipicephalus microplus strains and isolates from different statesof Mexico. in silico analysis of the amino acid sequence was performedin order to select a region of 145 amino acids. Subsequently, a pair ofspecific oligonucleotides was designed to amplify the fragment of interest ineach strain and isolate, obtaining a 435 bp amplicon. The products werecloned into the pCR®4-TOPO® vector and the plasmids transformed into the competent E. coli TOPO10® cells. Positive clones were selected forsequencing purposes. The results showed an identity percentage of 99.08% for the reference strain “Media Joya” with respect to the previously reported strain in Brazil (KC990116.1). The strains “Vargas”, “Hybrid”, “Huastecas” and the isolates from Campeche, Chiapas, Hidalgo, Morelos and Guerrero an identity and similarity percentage of 100% was observed. These results demonstrate a high degree of conservation in the sequence of the RmS-17polypeptide and suggests that it is appropriate to carry out the developmentof an immunogen that will be useful to control R. microplus infestations inseveral geographical areas of Mexico.